The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10238-012-0202-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokeratin 18 as a biomarker for gastric cancer

Abstract: Cytokeratin 18 (CK18) fragments are released into circulation during epithelial cell death. M30 (reflect caspase cleaved CK18 fragment) and M65 (reflect total CK18 fragment) enzyme-linked immunosorbent assay (ELISA) detects circulating CK18 fragments released during caspase-dependent or total cell death, respectively; thus, CK18 has the potential of being a biomarker for epithelial cancers. In the present study, we investigated the serum levels of M30 and M65 in patients with gastric cancer, determined correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Even with surgical management, the prognosis of gastric cancer is still unsatisfactory, with an estimated 5-year survival rate of 20–25% in China (Hartgrink et al, 2009). Considerable efforts have been made to determine the risk factors for gastric cancer and to identify biomarkers in order to enhance screening and early detection and to better predict the clinical outcomes (Saragoni et al, 2013, Tiberio et al, 2015, Oyama et al, 2013, Hiraki et al, 2011, Lv et al, 2015). In addition to intensified screening for early detection, it is of timely and clinical importance to find novel approaches to improve the prognosis and prolong the survival of patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Even with surgical management, the prognosis of gastric cancer is still unsatisfactory, with an estimated 5-year survival rate of 20–25% in China (Hartgrink et al, 2009). Considerable efforts have been made to determine the risk factors for gastric cancer and to identify biomarkers in order to enhance screening and early detection and to better predict the clinical outcomes (Saragoni et al, 2013, Tiberio et al, 2015, Oyama et al, 2013, Hiraki et al, 2011, Lv et al, 2015). In addition to intensified screening for early detection, it is of timely and clinical importance to find novel approaches to improve the prognosis and prolong the survival of patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these antibodies have a diagnostic potential, reflecting apoptosis and/or necrosis in various situations. Increased levels of caspase‐cleaved CK18 are detected in the serum of cancer patients , septic patients and patients with liver disease . In the present study, apoptosis and necrosis are investigated in patients with acute pancreatitis.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, much effort has been made to develop preliminary screening tests in easily accessible specimens. Serum cytokeratin 18, hypermethylation of Sox17 gene, S100A9/AAT in gastric fluid, proteomics approach, and serum metabolomics were reported as useful diagnostic biomarkers for gastric cancer . More recently, some studies identified miRNA‐378, miRNA‐451, miRNA‐486, and four up‐regulated GC‐associated miRNAs (miRNA‐17‐5p, miRNA‐21, miRNA‐106a, and miRNA‐106b), which also displayed higher expression levels in GC serum .…”
Section: Discussionmentioning
confidence: 99%